Relationship between the Human Development Index and its Components with Oral Cancer in Latin America - Brenda Yuliana Herrera-Serna; Edith Lara-Carrillo; Victor Hugo Toral-Rizo; Regiane Cristina do Amaral; Raul Alberto Aguilera-Eguía (Springer, 2019)
To evaluate the relationship between the Human Development Index (HDI) and its components with oral cancer (OC) in Latin America. Ecological study in 20 Latin American countries in 2010 and 2017, which evaluated the relationship between the Age-Standardized Rates (ASRs) of incidence and mortality from oral cancer and the following indicators: HDI, with its components (income, education, and health indexes); and the Gini and Theil-L indexes. Among the countries with the highest HDI, men from Brazil and Cuba had the highest incidence and mortality ASRs per 100,000 inhabitants (ASR incidence >7.5 and mortality >4.5). Among those with the lowest HDI, Haiti was the most affected country (ASR incidence >4.1 and mortality >3.0). The highest male:female ratio was in Paraguay in both years (incidence >3.5 and mortality >4.0). Mortality from oral cancer is negatively related to the global HDI in both years, with regression coefficients (95% confidence interval) being −5.78 (−11.77, 0.20) in 2010 and −5.97 (−11.38, −0.56) in 2017; and separate (independent) from the income [−4.57 (−9.92, 0.77) in 2010 and −4.84 (−9.52, −0.17) in 2017] and health indexes [−5.81 (−11.10, −0.52) and −6.52 (−11.32, −1.72) in 2017] (p < 0.05) in the countries with lower HDI. Oral cancer incidence and mortality rates vary both among and within Latin American countries according to sex, with a greater burden on men. The HDI is negatively related to mortality from oral cancer in the countries of medium and low HDI.